Interaction between Gold Nanoparticles and Blood Proteins to define Disease states - Peitinho, David Jorge Ligeiro (2018)
One of the most studied subjects in Bionanotechnology is the application of Gold Nanoparticles (AuNPs). These have unique optical and chemical properties and interact with proteins and other biomolecules forming dynamic (Protein-Corona) layers at the surface. These protein coronas are responsible for increased in vivo biocompatibility, and can be studied by multiple techniques, tracking for disease-specific protein profiles. In this work, 15 nm AuNPs were synthesized by the Turkevich method, and 40 nm AuNPs were provided. Sample concentration and size were determined by UV-Vis spectroscopy, exploiting the Surface Plasmon Resonance (SPR) effect. Successful surface functionalization was performed with the alkanethiol 11-mercaptoundecanoic acid (MUA) or a pentapeptide (CALNN), maintaining a negative global net charge and increasing overall stability. Bionanoconjugation with Bovine Serum Albumin (BSA) and Fibrinogen (Fib), with molecular weights of 66 and 340 kDa respectively, was performed and characterized by Agarose Gel Electrophoresis (AGE). Electrophoretic mobility was determined using image and video analysis performed by the eReuss software. Adsorption affinity constant were determined using the conjugation curves obtained in the AGE results, fitted using the Langmuir Isotherm, and resulted in (1.5 ± 0.1) x 10-2 (AuNP-MUA) for BSA conjugation, and (51.2 ± 4.7) x 10-2 (AuNP-CALNN) and (34.3 ± 1.2) x 10-2 (AuNP-MUA) for Fib conjugation. Bioconjugation of AuNP-CALNN with BSA was inconclusive. Competitive scenarios of a protein mixture favored Fib adsorption over BSA. Fib conjugation of 40 nm AuNPs showed multiple adsorption constants of (3 ± 0.7) x 10-2 and (9.7 ± 2.2) x 10-4 respectively. The eReuss software proved to be a powerful tool to analyze image results from electrophoretic runs, and the video analysis feature gives way to an innovative way of analyzing these experiments and extract further information on the Protein Corona stability. Fergusson Plot analysis and Light scattering techniques (DLS, NTA and ELS) were performed to determine hydrodynamic sizes and Zeta-Potential of bionanoconjugated samples.